2013
DOI: 10.1111/mpp.12037
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis reveals MATH gene(s) as candidate(s) for Plum pox virus (PPV) resistance in apricot (Prunus armeniacaL.)

Abstract: Sharka disease, caused by Plum pox virus (PPV), is the most important viral disease affecting Prunus species. A major PPV resistance locus (PPVres) has been mapped to the upper part of apricot (Prunus armeniaca) linkage group 1. In this study, a physical map of the PPVres locus in the PPV-resistant cultivar 'Goldrich' was constructed. Bacterial artificial chromosome (BAC) clones belonging to the resistant haplotype contig were sequenced using 454/GS-FLX Titanium technology. Concurrently, the whole genome of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 88 publications
1
60
0
Order By: Relevance
“…Therefore researches have focused on these three loci. Zuriaga et al (2013) sequenced and analyzed BAC clones corresponding to the ∼196-kbp PPVres loci and confirmed the presence of these three markers in the sequenced region. The potential of these three markers for MAS studies was investigated in several studies.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore researches have focused on these three loci. Zuriaga et al (2013) sequenced and analyzed BAC clones corresponding to the ∼196-kbp PPVres loci and confirmed the presence of these three markers in the sequenced region. The potential of these three markers for MAS studies was investigated in several studies.…”
Section: Discussionmentioning
confidence: 93%
“…We also used the SSLP marker ZP002, designed within the best candidate gene for the PPVres locus (Zuriaga et al . ; Decroocq et al . ).…”
Section: Methodsmentioning
confidence: 99%
“…Simultaneously, genomics-based crop breeding using NGS technologies is expected to overcome the challenge of feeding an increasing world population. As suggested by Varshney et al (2014), NGS technologies, which have rarely been applied to antiviral breeding using natural variants (Zuriaga et al, 2013; Mariette et al, 2016), would be quite useful for identifying loci in naturally resistant variants and also for breeding to introduce resistant loci into specific cultivars. Several studies have identified loci of interest from Arabidopsis mutants using whole-genome sequencing of pooled mutant F2 populations (Schneeberger et al, 2009; Austin et al, 2011; Uchida et al, 2011).…”
Section: Strategies For Improving the Genetic Resources For Recessivementioning
confidence: 99%